SURGICAL TREATMENT OF PRIMARY LOWER LIMB LYMPHEDEMA ASSOCIATED WITH VENOUS MALFORMATION: CASE REPORT AND LITERATURE REVIEW - Mendes, Daniel (2020)
Introduction: Lower limb lymphedema is a relatively common pathology that conditions a marked impact on the patient's quality of life. It may occur primarily or be secondary to an external factor. In most cases, its treatment is conservative through compression therapy. However, reconstructive surgery of the lymphatic system to improve lymphatic drainage have gained popularity. In the most severe cases, it may be necessary to perform excisional procedures for limb reduction. Methods: A review of a clinical case of severe lower limb lymphedema was performed, which was treated using a surgical procedure of debulking. Subsequently, a literature review was carried out using the MEDLINE database. Results: A 46-year-old male with a history of morbid obesity followed closely in the outpatient clinic by lymphedema praecox of the right lower limb that appeared in the second decade of life. The patient was observed at the vascular surgery consultation with complaints of lymphorragy, and conservative treatment with compressive therapy was instituted. Despite the initial improvement, a lymphedema worsening was observed with recurrence of lymphorragy in the thigh. He underwent debulking surgery with a favorable outcome and marked clinical improvement in the postoperative period. Conclusion: Lymphedema of the lower limbs is a poorly recognized condition that has a marked impact on patients' quality of life. Currently, there is no curative treatment and the results of conservative treatment are limited. Surgical treatment, especially excisional procedures, are used in the most serious cases, mainly to treat complications associated with the chronicity.